Temperature and Mask Detector using Thermal Camera and Open CV based on Color Features - Hendi Purnata; Zaeurrahman; Hera Susanti; Asni Tafrikhatin (Jurnal E-Komtek, 2022)
The current situation demands the prevention of the spread of the virus, one of which is by wearing a mask and checking the body temperature. This paper serves as a means of detecting the body temperature by using a thermal camera and the mask with a web camera. The camera is the sensor, and a buzzer is an actuator that go off automatically. A mask detection device is a tool that detects visitors who wear masks. It works by detecting the visitor's face using a camera and Open CV or digital image processing. Then, the data will be processed and compared to the one that has been input into the program. This program is able to detect masks and provide warnings if the visitors do not wear masks in a public space. When the body temperature detector detects a visitor of the normal category, which is 36˚C - 37.5˚C, the buzzer does not go off; when the body temperature is higher than 37.5˚C, the buzzer goes off automatically. An error occurred due to the dark conditions, and from the five trials with 100 cm distance, 60% of the trials were successful. Therefore, it was concluded that the testing of the mask detector succeeded with more than 60% success when the lighting was sufficient; and the distance ranged from 100 cm. This system experiment with five experiments on each sample obtained pretty good results. To get good results, the light determination is very influential.